Comparing SMART and ELECTRE methods for multi-criteria decision analysis: A case study evaluating conservation strategies - David M. Martin; David R. Smith (Environmental and Sustainability Indicators, 2025)
Tradeoffs are part of the inherent challenge of making decisions. Defaulting to a prevalent method can mask methodological variation and potential improvement in decision quality. We applied and compared methods for multi-criteria decision analysis (MCDA) in real-world environmental planning. Decision makers at a global conservation organization formed teams to review and prioritize the allocation of resources across a set of existing strategies across seven teams. Each team evaluated and rated strategies based on a common scale composed of weighted objectives and criteria. Sensitivity analysis included implementing two different MCDA methods, varying strategy ratings, and using two different criteria weighting techniques. The MCDA methods were SMART (Simple Multi-Attribute Rating Technique) and ELECTRE (ELimination and Choice Expressing The REality). We tested user satisfaction between methods, overall rankings between methods, and whether MCDA improved the decision-making process. The methods did not differ in most comparisons, although participants were more likely to use the SMART method in future tradeoff decisions. We found evidence of rank correlation between methods. Lastly, the teams’ final recommendations were consistent with MCDA results. This study highlights the advantages and disadvantages of MCDA in real-world applications.